Pengaruh Pemberian Madu terhadap Hasil Daya Tahan Jantung Paru, Daya Tahan Otot, dan Power pada Atlet Rowing Kota Bandung - Rizkyrullah, Nauval Irfan; Tarigan, Beltasar; Wijayanti, Kurnia Eka (SPRINTER: Jurnal Ilmu Olahraga, 2024)
In this study, researchers aimed to find out the effect of giving honey on cardiorespiratory endurance, muscle endurance and power in rowing athletes in Bandung City. This study uses a quantitative approach. Experimental method, using a pretest-posttest control group design form through 3 stages, pretest, treatment, and posttest. Researchers used a rowing ergometer test with a distance of 2000 meters and 100 meters. This research involved 14 rowing athletes from the city of Bandung. Sampling used purposive sampling technique. Hypothesis testing uses SPSS version 27 with paired simple t test and independent simple t test techniques. The results showed that giving honey had an influence on cardiorespiratory endurance, muscle endurance and power in rowing athletes in Bandung City.